Carbono total e abundância natural de 13C em perfis de solo sob plantio de eucalipto - Severo, Fabiane Figueiredo (2017)
The planting of eucalyptus is a common practice in areas previously used for extensive livestock farming in the southern half of Rio Grande do Sul (RS), but such cultivation raises many questions about its influence on the dynamics of soil organic matter (SOM). An evaluation was made possible due to the photosynthetic cycle of eucalyptus, which as in other tree species are C3 and in most grasses is C4. C4 cycle plants use 13C (carbon heavy isotope) in photosynthesis, while plants with C3 cycle make distinction of 13C of the air, generating MOS with different isotopic abundances. This study evaluated the overall carbon content and the isotopic abundance of 13C in soil profiles under eucalyptus plantation of different ages (2, 10 and 21), in a natural regeneration area and natural grass field as well as estimated the contribution to the conversion of SOM according to each vegetation. The initial management of all sampled areas was natural pasture. In profile the following layers were evaluated: 0-5, 5-10, 10-20, 20-30, 30-40, 40-50, 50-70 and 70-90 cm. The 13C isotopic abundance of soil and plant tissue was performed by mass spectrometry. After two years of planting eucalyptus, the surface layer showed an increase of carbon relative to its subsurface layer and the beginning of pasture carbon conversion process possibly has begun to occur in this surface layer (0-5 cm). In 10 years of planting it occurred a decrease of SOM between the layers until the initial 20 cm and the MOS conversion process between pasture and eucalyptus shows up to this depth. After 21 years of planting, the whole profile has undergone change by planting eucalyptus trees, taking in its surface layer the higher carbon value from the eucalyptus cultivation (90.4%). In the area where there was a natural regeneration, the higher carbon content in the surface layer was observed (3.53%) and this may be due to the greater diversity of the chemical composition of the deposited material. In this area, there are indications that the MOS cycling process has reached all the profile layers through the waste contributed by the native tree species.